The mediating role of organizational commitment of job performance: The Impacts of Leadership, job competency and organizational culture - ., Suriadi; Gani, Mursalim Umar; Muh, Nasir Hamzah; Arifin, Zainal (Archives of Business Research, 2018)
The purpose of this paper is to examine the mediating role of organizational commitment of job performance: The Impacts of leadership, job competency and organizational culture. Data were gathered through questionnaires. Data collected from 254 employees working on the eight work units on the Southeast Sulawesi regional government office. The structural equation modeling (SEM) results indicate that: (1) leadership, job competence, and organizational culture partially have a direct effect on organizational commitment, (2) leadership, job competence, and organizational culture partially have a direct effect on job performance, (3) leadership, job competence, and organizational culture partially have a direct effect on job performance, with the mediating role of organizational commitment.